Psychobiological processes in health and illness - Hamilton-West, Kate. (Los Angeles : SAGE, 2011)
An accessible and engaging introduction to the interrelationships between mind and body across a broad range of topics, including infectious illness, autoimmunity, cancer and pain. Taking a biopsychosocial approach, it brings together research from a number of disciplines including health psychology, psychoneuroimmunology and behavioural genetics.
Mind-body connection -- Link between stress and illness -- Positive processes in health and illness -- Healthy disposition -- Pain -- At risk populations -- Psychobiological interventions -- Methodological issues in psychobiological research -- Summary and future directions.
Includes bibliographical references and index.
Keywords: Psychobiology; Psychophysiology; Biological Psychiatry; Pain -- psychology; Psychotherapy; Biological psychiatry; Pain -- Psychology